Ativismo contra a pena de morte: Um estudo sobre as denúncias no Sistema Interamericano de Direitos Humanos (SIDH) contra os países caribenhos membros da Commonwealth (1970 – 2020) - Custódio, Tuane Fonseca (2021)
This research aims to present the study’s results on activism against the death penalty in complaints against Caribbean Commonwealth countries in the Inter-American Human Rights System. Therefore, a mixed quantitative and qualitative research was carried out, which gathers information on the reports on admissibility, inadmissibility, merits and archive in the IACHR, as well as the cases addressed to the I/A Court H.R. The information collected allowed to identify that the legal activism that targets the inter-American system is of foreign individuals (lawyers) and private organizations (law firms), most of them from the United Kingdom, without domestic coalitions and that use the interplay between the IAHRS and the Commonwealth’s Judicial Committee of the Privy Council and the Caribbean Court of Justice. These characteristics are, in part, explained by the institutional heritage from the colonial period. The results were analyzed from the perspective of the reference literature in transnational legal activism studies, especially the works of Keck and Sikkink (1998) and Tarrow (2005).